Packaging for nonthermal processing of food - Pascall, Melvin, 1954-; Han, Jung H. (John Wiley & Sons, Inc., 2018)
Revised and updated for the first time in a decade, this book discusses packaging implications for recent nonthermal processing technologies and mild food preservation such as high pressure processing, irradiation, pulsed electric fields, microwave sterilization, and other hurdle technologies. It reviews typical nonthermal processes, the characteristics of food products after nonthermal treatments, and packaging parameters to preserve the quality and enhance the safety of the products. In addition, the critical role played by packaging materials during the development of a new nonthermal processed product, and how the package is used to make the product attractive to consumers, is discussed.- Resumé vydavatel
Keywords: balení potravin; konzervování potravin; food packaging; food preservation; elektronické knihy; sborníky; electronic books; papers of several authors